The International Algebraic Conference dedicated to the 100th anniversary of L.A. Kaluzhnin - Drozd, Yu.; Kirichenko, V.; Petravchuk, A.; Sushchansky, V.; Ustimenko, V. (Algebra and Discrete Mathematics, 2015)
The International Algebraic Conference dedicated to the 100th anniversary of an outstanding mathematician and teacher, the founder of Algebra and Mathematical Logic Department of Taras Shevchenko National University of Kyiv Professor L.A. Kaluzhnin was held on 7–12 July 2014 in Kyiv.